PENGARUH KOMPETENSI KEPRIBADIAN GURU DAN MOTIVASI DARI GURU TERHADAP HASIL BELAJAR SISWA KELAS IX DI SMP SWASTA TELADAN PEMATANG SIANTAR - Natallia Christina Sinambela; Benjamin Albert Simamora; Sotarduga Sihombing (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 21. The population in this study was 75 people, and the sample used was 75 people. The sample collection technique used was the total sample. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2). The results of this research state that: 1) there is a positive influence of teacher personality competence on student learning outcomes. This result can be seen in the t test where the t value of teacher personality competence (3.108) > t table value (1.993). 2) there is no positive and significant influence of student motivation on student learning outcomes, this result can be seen in the t test where the t value of student learning interest (0.006) > t table value (1.993) which means this variable is not significant. 3) teacher personality competence and learning motivation together influence student learning outcomes, these results can be seen in the F test where the Fcount value (11.125) > Ftable value (3.12). The R square coefficient of determination test was found to be 0.236, which means that 23.6% of the variables of teacher personality competence and student motivation on student learning outcomes are on the learning outcomes of class 9 students at the exemplary private junior high school in Pematang Siantar, and 76.4% is the influence of other variables that are not examined in this research.